PENGARUH HARGA DAN FASILITAS TERHADAP KEPUASAN PELANGGAN PADA GUEST HOUSE HUMANITAS PEMATANGSIANTAR - Anggun Lestari; Darwin Lie; Efendi Efendi; Julyanthry Julyanthry (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2018)
The results of this study can be summed summarized as follows: 1. The prices is good, facilities is good and satisfied customers are already satisfied. 2. Regression analysis result is Ŷ = 9,342 + 0,927X1 + 0,173X2,it means there is a positive influence between price and facilities to customer satisfaction. 3. The results of the correlation coefficient analysis obtained value r = 0,819, which means there is a high and positive correlation between price and facilities with customer satisfaction. Obtained value of coefficient of determination = 0,670, meaning that high of customer satisfaction equal to 67% can be explained by price and facility. 4.Hypothesis test result stated H0 rejected, it means the prices and facilities have a positive and significant impact on customer satisfaction at Guest House Humanities Pematangsiantar both simultaneously or partially.The suggestion of this research 1. to streamline the price on the dimension of the payment method, we recommend that you open a bank account in the name of the guest house so as to facilitate payment transactions credit. 2. to improve facilities, guest house should pull out some chairs or tables are not needed in order to avoid the impression of a cramped room at the lobbi. 3. to improve customer satisfaction, we recommend guest house makes guest house website which features a floor plan of the signposts towards the guest house, making it easier for customers to find the location of the Guest House. Keywords: Price, Facilities, Customer satisfaction.